Identity and sustainability of 'Chuangzuo' music movements as observed through case studies on 'Gongzuofang' music groups in Penang, Malaysia - Chow, Ow Wei (2008)
Chuangzuo has emerged as a music trend through a music movement, and as a popular culture for youth in Malaysia, but the music of chuangzuo have not been described to the general public that is probably not aware of the identity in chuangzuo, the social aspects of chuangzuo as in a gongzuofang, and also how the music has sustained so far. The primary objective of this study is to determine the identity and the sustainability of chuangzuo activities in Malaysia. The specific objectives are to produce a description on the settings of gongzuofang in Penang, an analysis of musical materials of chuangzuo, and a clarification of the identity and sustainability of chuangzuo based on the former two specific objectives. Observation through fieldwork is rendered for this ethnographic research. The primary setting is gongzuoJang in Penang, namely the Wanderers and CZMusic which have been actively involved in chuangzuo activities. Observation, interviews and video recordings of important rehearsals and actual performance were rendered. The secondary setting of the fieldwork is based on related song-writing competitions, concerts and music camp, which were held in Penang and Kuala Lumpur. The general phenomenon of chuangzuo depicts a scene where youth perform their own music compositions with guitars or light instruments. Chuangzuo is a music activity for the youth in Malaysia, as the music, mainly performed in Chinese, often depicts the youth's life-cycle events. The music is commonly composed in the sentimental style or of a ballad that usually adopts a major key and the common simple quadruple time. Instrumentation is usually simple, and Chinese texts· with rhymes are used. Though mixed language and vocables are included sometimes, the texts are commonly written in the discursive style. A gongzuofang is the basic unit of chuangzuo that accommodates youth's music activities. It exists as an important space for music practice, music learning, idea-sharing, planning, music presentation, socialisation, and also life-cycle events. The studied gongzuofang represents a typical organisation that provides its members with abundant opportunities in musi ccompositions, as members learn to compose, perform, compete in music contests and produce music concerts or music recording. Chuangzuo is an opportunity for youth to engage with music. They usually adopt elements of cultural fusion in their compositions, and they show amateurish characteristics in their music. This has formed the musical identity of chuangzuo. The social identity of chuangzuo is built through identity construction, individuality, communion formation and aspiration. Nevertheless, the need to survive changes for the long term has triggered the implementation of sustainability in the handling of chuangzuo. The sustainable ways, as observed, are organisation, commercialisation, hegemony and exclusion of certain music genres.